Menumbuhkembangkan Sikap Religi Pada Anak Usia Dini Melalui Pembiasaan Membaca Doa Harian di TK Negeri Meleber Kec. Meleber Kab. Kuningan - Khumairaa, Rizqika; Asep Nugraha, Sopian (Diksi: Jurnal Pendidikan dan Literasi, 2024)
The formation and development of religious attitudes in early childhood can be done by shaping their morals. Of course, the right method is needed for this. The purpose of this research is to develop the religious attitude of AUD through the habituation method. The research method used was descriptive qualitative. The research participants were teachers in Group B of Meleber Kindergarten. The results showed that the method of habituation of prayer and reading daily prayers is very effective and efficient to be implemented in Group B AUD at TKN Meleber. Teachers must also have skills in using this habituation method, namely in the form of harmony between speech and action so that AUDs easily understand and are well imprinted in themselves.